2010
DOI: 10.1097/coc.0b013e31819ccc8c
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery With or Without Whole Brain Radiotherapy for Patients With a Single Radioresistant Brain Metastasis

Abstract: Gamma Knife SRS is a safe and feasible strategy for treatment of patients with a single radioresistant brain metastasis. Radiosurgery alone is a reasonable treatment option, but may carry a greater likelihood of distant brain recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…Overall, the distribution of tumor volumes in our cohort were relatively small, with the rationale for using SRT related to eloquent tumor location in most cases, and therefore large size was not likely a factor reducing local control. With regard to histology, approximately 5 % of patients enrolled on the RTOG 95-08 and EORTC prospective trials had melanoma [2,3], which is significantly lower than in the present study, and this histology has been linked to greater radioresistance [23], though not in all studies [1,4], and was not associated with more aggressive local progression in our study. A recent study found that while local control after singlefraction SRS was similar between classically radiosensitive versus radioresistant brain metastasis histologies, SRT for radioresistant histologies demonstrated worse local control than for radiosensitive histologies, with an odds ratio of 5.37 (95 % CI 3.83-6.91; p = 0.032) [24].…”
Section: Discussionmentioning
confidence: 46%
“…Overall, the distribution of tumor volumes in our cohort were relatively small, with the rationale for using SRT related to eloquent tumor location in most cases, and therefore large size was not likely a factor reducing local control. With regard to histology, approximately 5 % of patients enrolled on the RTOG 95-08 and EORTC prospective trials had melanoma [2,3], which is significantly lower than in the present study, and this histology has been linked to greater radioresistance [23], though not in all studies [1,4], and was not associated with more aggressive local progression in our study. A recent study found that while local control after singlefraction SRS was similar between classically radiosensitive versus radioresistant brain metastasis histologies, SRT for radioresistant histologies demonstrated worse local control than for radiosensitive histologies, with an odds ratio of 5.37 (95 % CI 3.83-6.91; p = 0.032) [24].…”
Section: Discussionmentioning
confidence: 46%
“…Patients with RCC may experience symptomatic improvement with whole brain radiation therapy, but RCC is considered to be radio-resistant in nature because of its poor response to standard radiation therapy. The 1-year intracranial local control rate is estimated to range from 0% to 14% [16]. In contrast, stereotactic radiosurgery for brain metastasis of RCC reportedly offers good control of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a paradigm shift toward more focused radiation treatment. For patients with limited brain metastases, SRS can be used as an alternative to WBRT without compromising overall survival, and with reduced neurocognitive impairment (83)(84)(85)(86). Due to better response of melanoma to large radiation fraction dose, SRS treatment significantly improved the local control rate of melanoma brain metastases compared to those that were treated with WBRT (87,88).…”
Section: Role Of Palliative Rt For Melanomasmentioning
confidence: 99%
“…Due to better response of melanoma to large radiation fraction dose, SRS treatment significantly improved the local control rate of melanoma brain metastases compared to those that were treated with WBRT (87,88). The 12-month local control rate with SRS is about 65% (85)(86)(87)(88). More impressively, SRS also contributes to improved overall survival from 4 months to 6-8 months as compared to WBRT (85,89,90).…”
Section: Role Of Palliative Rt For Melanomasmentioning
confidence: 99%